Nature-Culture Binary versus Ancient Folklore of Bihar (An Eastern Indian State) - Mallika, Tosha; Dwivedi, Rajiv Ranjan (Classical Literature, 2024)
The research article utilizes the ancient folklore of Bihar to build an enhanced perspective on the relationship between culture and nature. Different legends, folk-beliefs, and folk practices have played an immense role in the generation of this analysis. The folklore of the Angika region as shown in the map is the primary source. The terms Angika and Ang Pradesh have both been famous in the ancient epic Mahabharata. Ang Pradesh is the abode of the warrior Karna, a prominent recurring figure in the epic. The researchers travelled to suburbs to interview the natives and document folklore. Whether nature culture could stagnantly be called binaries, is one of the central questions that the present research intends to answer.